Fokale Läsionen in der Ganzkörper-MRT beim multiplen Myelom: Quantifizierung der Tumorlast und Korrelation mit krankheitstypischen Parametern und Prognose = Focal lesions in whole-body MRI in multiple myeloma : quantification of tumor mass and correlation with disease-related parameters and prognosis - Brandelik, Simone Christine; Hielscher, Thomas; Hillengaß, Jens; Kloth, Jost; Kauczor, Hans-Ulrich; Weber, Marc-André (Der Radiologe, 2018)
Background and objectives: In this study, we evaluated methods of quantification of tumor mass in whole-body MRI (wb-MRI) in multiple myeloma and correlated these with disease-related parameters in serum and bone marrow. Materials and methods: We retrospectively evaluated wb-MRIs of 52 patients with focal infiltration pattern and a total of 700 focal lesions (subsequently called lesions). We determined the longest diameter (LD), the segmented volume (SV), and the morphology (spherical or non-spherical). We correlated total number/volume of the lesions with clinical parameters and prognosis and furthermore LD with SV. After that we analyzed the agreement of SV and estimated volume (EV) using the volume formula of a sphere based on LD. Results: Results showed no significant correlations of total number/volume with prognosis or clinical parameters. The latter were situated predominantly in the normal range. Furthermore, 10% of lesions were spherical. SV and LD correlated significantly in single lesions and on patient level. SV was in lesions <6 cm3 systematically larger and in lesions ≥6 cm3 smaller than EV. In 95%, we found in small lesions a deviation of EV versus SV from +0.9 cm3 to −4.6 cm3 and in large lesions from +160 cm3 to −111 cm3 (EV-SV). Conclusions: Quantification of tumor mass in the focal infiltration pattern is performed more accurately by volumetry than LD due to the predominant existence of non-spherical lesions. The patient cohort with clinical parameters predominantly in the normal range is distributed to ISS stage I and partly pretreated, a fact that makes interpretation of absent correlations more difficult. Consider also a variation in activitiy of lesions and a diffuse infiltration not detectable by MRI.